Meningkatkan Kemampuan Kosakata Bahasa Arab Melalui Media : Improving Arabic Vocabulary Skills Through Media - Walidain , Hilyatul; Buhaerah, Buhaerah (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2023)
The learning process arises from the mutual influence between humans and their environment. Arabic language learning is a subject that aims to develop, encourage, direct, guide, and develop skills and positive attitudes towards responsive and productive Arabic. Vocabulary teaching is usually done by prohibiting vocabulary and its meaning in context. It can be understood, through analyzing vocabulary, when banning the meaning of parts of words and restricting the meaning of words directly from the list of words made. This research employs a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The effectiveness of learning media in Arabic language education depends on its alignment with the subject's objectives, highlighting the importance of tailored media selection based on educational institution needs and press availability. Visual aids like pictures can enhance the recognition of Arabic vocabulary and facilitate understanding through visual representation. Proses pembelajaran timbul dari saling pengaruh antara manusia dan lingkungannya. Pembelajaran bahasa Arab adalah subjek yang bertujuan untuk mengembangkan, mendorong, membimbing, dan mengembangkan keterampilan serta sikap positif terhadap bahasa Arab yang responsif dan produktif. Pengajaran kosakata biasanya dilakukan dengan melarang kosakata dan maknanya dalam konteks yang dapat dipahami, melalui analisis kosakata saat melarang makna bagian kata dan melarang makna kata langsung dari daftar kata yang telah dibuat. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Efektivitas media pembelajaran dalam pendidikan bahasa Arab tergantung pada kesesuaian dengan tujuan subjek, menekankan pentingnya pemilihan media yang disesuaikan berdasarkan kebutuhan lembaga pendidikan dan ketersediaan media. Bantuan visual seperti gambar dapat meningkatkan pengenalan kosakata Arab dan memudahkan pemahaman melalui representasi visual.